Pembangunan Aplikasi Honda Care sebagai Sistem Perawatan Sepeda Motor menggunakan Metode Prototyping (Studi Kasus pada AHASS di Kota Malang) - Wisnu Galih Pradita; Adam Hendra Brata; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Engine oil is the most vital element in motorcycle maintenance. Due to ignorance about the time of engine oil change can cause engine performance to decrease even turn off the engine flame. In addition, the maintenance of motorcycles is less understood by some motorcycle owners in Malang with a percentage of 64.4%. As many as 68.6% admitted if the motorcycle has branded Honda. This data is obtained by the author with the questionnaire technique through google form. With these problems, the author conducted research on the development of software Honda Care as a motorcycle maintenance application using prototyping method with case studies on AHASS in Malang. In the process, done as much as 2 times iteration. This research will produce mobile applications connected to embedded systems in the form of vertical water buoy sensor and NodeMCU. Applications are tested to Motorcycle Owners by testing user acceptance. The test result is 86.3% for software engineering aspect, 89.7% for aspect of functionality and 88.6% for visual communication aspect. The results indicate excellent acceptance from Users and will serve as reference as evidence that the Honda Care application has been completed and is acceptable to Users.